Содержание азота в листьях древесных растений и их повреждаемость - индикационные показатели эмиссионных воздействий химкомбината по производству азотных удобрений - Коршиков, И.И.; Игнатенко, А.А.; Виноградова, Е.Н. (Промышленная ботаника, 2003)
Research on injuries in 43 arboreous species caused by emissions of a chemical enterprise specializing in nitrogenous fertilizers production has been conducted by way of two-year observations. It indicated a high specific heterogeneity in a degree and character of plant injuries due to air pollutants. As a rule, a higher nitrogen content and the increased total pool of free aminoacids was noted in the lives under the conditions of intensive air pollution caused by the toxic nitrogen bearing gases. However, only the excessive accumulations of non-protein nitrogen in leaves is to a certain extent indicative of air pollution due to toxic gases and the strength of their effect on plants. The research conducted allowed to determine the arboreous plants which can by employed for monitoring of air pollution caused by the emissions of chemical enterprises.